Photo-inhibition Effect from Strong Electron Withdrawing Nitro Group in N-[(E)(4-Bromophenyl)Methylidene]-4 Nitroaniline - Yuvaraj, A. R.; Lutfor, M. R.; M. M., Yusoff; Mohammed, Suliman (ISSR Publishing, 2016)
Light induced effect of N-[(E)-(4-bromophenyl)methylidene]-4nitroaniline was investigated using UV-Vis spectrophotometer. This study revealed that the presence of strong electron withdrawing nitro group inhibited the photo-reactivity of the compound. Mainly, molecular structure and functional groups have tremendous influence on chromophoric compounds. The photoisomerization effect was not found in this compound, due to the photo-inhibition of nitro group present in the molecular system.